Antigenic quantitation of type 1 fimbriae on the surface of Escherichia coli cells by an enzyme-linked immunosorbent inhibition assay. - Dodd, D C (1982)
Type 1 fimbriae from two strains of Escherichia coli, K-12-derived CSH50 and a clinical isolate VL-2, were purified by a simplified procedure, which should be applicable to a variety of bacterial strains. After mechanical removal from the cells, the fimbriae were sedimented in the ultracentrifuge and resuspended in 5 M urea to disaggregate cell membranes and flagella, leaving the urea-resistant fimbriae intact. After several hours at 37 degrees C, this crude fimbrial suspension was diluted to 1 M urea, and the intact fimbriae were sedimented through a 1 M urea-1 M sucrose cushion. The pellet was found to be pure fimbriae by sodium docecyl sulfate-polyacrylamide gel electrophoresis, with apparent subunit molecular weights of 17,000 for the fimbriae from K-12 strain CSH50 and 19,000 for those from the clinical isolate VL-2. High-titer rabbit antiserum raised against CSH50 fimbriae was specific for fimbriae by indirect ferritin labeling and immunoprecipitation and was used to develop an enzyme-linked immunosorbent assay. Competitive inhibition of antifimbrial antiserum in the enzyme-linked immunosorbent assay by a known amount of either purified fimbriae or fimbriae-bearing bacteria permitted precise quantitation of fimbrial antigen in cultures of strain CSH50, thereby providing a simple means of determining the effects of environmental conditions on the synthesis of type 1 fimbriae.